Consequences of measurement error for inference in cross‐lagged panel design—the example of the reciprocal causal relationship between subjective health and socio‐economic status. (15th September 2015) - Kröger, Hannes; Hoffmann, Rasmus; Pakpahan, Eduwin
Abstract : We discuss the problem of random measurement error in two variables when using a cross‐lagged panel design. We apply the problem to the question of the causal direction between socio‐economic status and subjective health, known also as health selection versus social causation. We plot the bias of the ratio between the social causation and the health selection coefficient as a function of the degree of measurement error in subjective health and socio‐economic status for different scenarios which might occur in practice. Using simulated data we give an example of a Bayesian model for the treatment of measurement error that relies on external information about the degree of measurement error.